Factors affecting the quality of postgraduate medical education in Pakistan – residents’ perspective - N. Qureshi, Aneeqa; Bano, Roohi; Younas, Saliha; Razia, Eesha; Azmat, Maham; Ramzan, Hussain (International Journal Of Community Medicine And Public Health, 2025)
Background: Postgraduate medical education (PGME) plays a crucial role in healthcare workforce development. In developing countries like Pakistan, PGME has seen significant advancements, particularly through institutions such as the College of Physicians and Surgeons. However, challenges persist in ensuring high-quality training. This study aims to explore factors affecting the quality of PGME, including pre-training support, training structure, research opportunities, soft skills development, and workplace environment. Methods: A cross-sectional survey was conducted among 116 postgraduate residents from various hospitals in Punjab, Pakistan. Data was collected using a structured questionnaire, analyzing demographics, training structure, research opportunities, soft skills, and workplace support. Descriptive and inferential statistical analyses were performed, with a chi-square test used to identify significant associations. Results: The study revealed inadequate pre-training support, with only 19.8% of residents receiving academic or assessment regulations before training. Dissatisfaction with the training structure was prevalent, particularly regarding trainer-to-trainee ratios and feedback mechanisms. A lack of integration of research opportunities within training was noted, with 40% of residents reporting insufficient skills. While 66% reported positive impacts on medical knowledge, soft skills development was inadequately addressed. Significant concerns regarding workplace social support, including gender discrimination and inadequate facilities, were highlighted. Statistically significant associations were found between specialty and factors such as pre-training support, soft skills, and workplace support (p<0.05). Conclusions: The findings emphasize the need for systematic improvements in PGME, particularly in pre-training orientation, mentorship, structured research opportunities, and workplace culture. Addressing these issues through targeted interventions can enhance the training experience and outcomes for postgraduate residents in Pakistan.